Evaluating lake ecosystem health using fish as a bioindicator and its relation to water quality at Subang Lake, Selangor, Malaysia - Chai, Xeai Li (2021)
Subang Lake, Selangor is an endorheic lake that is surrounded by a forest area, however, rapid urbanization is being developed around Subang Lake. Biomonitoring act as an important technique to monitor the changes in the environment. The objectives of this study are to determine ecological and fisheries indices of Subang Lake, water physicochemical parameters of Subang Lake, and the relationship between fish assemblages and water physicochemical parameters of Subang Lake. In this study, seven sampling points have been selected in Subang Lake which is easily accessible and recommended by the staff from Pengurusan Air Selangor Sdn. Bhd. Five gill nets with different mesh sizes and two fish traps were set at each sampling point in the morning at 0800h and were checked every four hours until 1800h. The nets were set overnight on four consecutive days and the results of the captured freshwater fishes were recorded. The fish sampling was conducted within the month of July 2018, August 2018, June 2019, August 2019, and October 2019. The water physicochemical parameters were determined using the standard methods for the examination of water and wastewater. In-situ water parameters such as dissolved oxygen, pH, temperature, turbidity, and electrical conductivity were measured at Subang Lake. While the ex-situ water parameters such as ammoniacal nitrogen (NH3N), nitrate (NO3N), nitrite (NO2N), phosphate (PO4), biochemical oxygen demand (BOD5), and chemical oxygen demand (COD) were measured by conducting a laboratory analysis. Water sampling was conducted within the month of June 2019, August 2019, and October 2019. A total of 1266 individuals of fish which belong to 9 families and 19 species were recorded in Subang Lake. There were five alien species that were recorded in this study. A higher number of species and individuals of fish were found in October 2019. However, there is nosignificant difference in the number of fish individuals and fish species in both spatial and temporal variation. Meanwhile, the length-weight relationship of Cyclocheilichthys apogon (b=2.884) and Notopterus notopterus (b=2.886) indicates that these fish species are negative allometric growth. However, the condition factor of Cyclocheilichthys apogon (Kn=1.184) and Notopterus notopterus (Kn=1.010) indicate good general condition. Apart from that, the water quality of Subang Lake falls into category A where the water quality is suitable for conventional use but requires water treatment. The water quality is suitable for sensitive aquatic species. In this study, there is significant relationship between fish assemblages and water physicochemical parameters. The continuous measurement between the fish assemblages and water physicochemical parameters acts as an important factor in biomonitoring of Subang Lake. In conclusion, the ecosystem health of Subang Lake is currently varied, i.e., from moderate to good condition. However, improvement of the management and conservation of the aquatic and terrestrial ecosystem surrounded the need to be concerned about Subang Lake, so that the ecosystem health of Subang Lake can be protected and maintain.